Modeling the exchange rates of the Iraqi dinar against the dollar in the Central Bank of Iraq for the period (2004-2021) - Dhad صبيحة نعمة (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The research aims to build an efficient standard model for the exchange rates of the Iraqi dinar against the US dollar in the Central Bank of Iraq, which is reliable in forecasting the coming periods, and by applying the steps of building the model using the (Box-Jenkins) method, a standard model for exchange rates was built and based on the (Eviews 9) program in Analysis of the monthly data obtained from the Central Bank of Iraq for the period (2004:01-2021:07) and after measuring the dormancy of the time series by the Dickie-Fuller test (ADF) and the Phillips-Peron test (PP), and revealed the existence of the problem of heterogeneity of variance in the time series Financial fluctuations abound, and after testing the estimated model, the best AR (1) model with GARCH (1,1) errors was accepted as an efficient model that could be relied upon in forecasting the coming time periods. And through the comparison criteria (AIC, H-Q, SCH) and the significance of the estimated parameters of the model, as it achieved the lowest values of the mentioned criteria.